2005
DOI: 10.1111/j.1600-6143.2005.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Recognition of MHC Class I Allopeptides Accelerates Lung Allograft Rejection in Miniature Swine

Abstract: The role of indirect allorecognition in graft rejection is examined in two experiments using a swine lung transplantation model. First, two swine received class I mismatched grafts without immunosuppression; another two recipients were treated postoperatively with cyclosporine (CsA). These swine exhibited acute and chronic rejection, respectively. All four recipients developed T-cell reactivity to donor-derived class I major histocompatibility complex (MHC) peptides. Second, six swine were immunized with synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
(51 reference statements)
1
17
0
Order By: Relevance
“…Analysis of lymphocytes extracted from recipient nodal tissue in these experimental constructs confirmed the presence of a small population of self-restricted T lymphocytes that were able to respond to donor-derived peptides (11). More recent experimental studies have shown that pre-transplant immunization with donor-derived MHC allopeptides can accelerate heart and lung allograft rejection and vasculopathy in both murine (12)(13)(14) and porcine systems (15,16). In the clinical arena, many investigators have demonstrated a positive correlation between T-cell reactivity to synthetic allopeptides derived from the donor MHC and chronic graft rejection and dysfunction.…”
Section: Alloantigen Recognitionmentioning
confidence: 91%
“…Analysis of lymphocytes extracted from recipient nodal tissue in these experimental constructs confirmed the presence of a small population of self-restricted T lymphocytes that were able to respond to donor-derived peptides (11). More recent experimental studies have shown that pre-transplant immunization with donor-derived MHC allopeptides can accelerate heart and lung allograft rejection and vasculopathy in both murine (12)(13)(14) and porcine systems (15,16). In the clinical arena, many investigators have demonstrated a positive correlation between T-cell reactivity to synthetic allopeptides derived from the donor MHC and chronic graft rejection and dysfunction.…”
Section: Alloantigen Recognitionmentioning
confidence: 91%
“…[1][2][3][4] For instance, immunization with allogeneic HLA peptides presented by acceptor HLA class II significantly increases both acute and chronic rejection after organ transplantation. 5 In addition, CD4 ϩ T-cell help is necessary to facilitate full differentiation of graft-infiltrating CD8 ϩ T cells. [6][7][8] However, other studies have pointed to a protective role of alloreactive CD4 ϩ T cells, which are able to mediate immunologic tolerance to the graft.…”
Section: Introductionmentioning
confidence: 99%
“…Allan has developed a miniature swine model of orthotopic lung transplantation which develops the spectrum of histopathological changes seen in human chronic lung rejection; this model has the benefit of allowing for surveillance biopsies that is not feasible in smaller animal models [54]. This group has used the miniature swine model to study the role of indirect allorecognition in developing CLAD [55]. Atanasova performed rat orthotopic lung transplants in the Fischer 344 → Lewis strain combination, treated the recipients with cyclosporine postoperatively and instilled lipopolysaccharide into their airways on postoperative day 28; this resulted in pulmonary fibrosis and fibroproliferation of airways resembling human BO [56].…”
Section: Experimental Models Of Cladmentioning
confidence: 99%